Aerogel composite sheet and preparation method thereof
By using aerogel composite sheet composed of silica aerogel and phase change microcapsules on the battery pack of new energy vehicles, the battery pack's endurance and thermal runaway problems in low temperature environments are solved, and efficient isolation is achieved Thermal and flame retardant properties simplify production processes and reduce environmental pollution.
Patent Information
- Application Number
- CN202411134723.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-01-03
AI Technical Summary
The battery pack of new energy vehicles has reduced its endurance in low temperature environments, and is prone to thermal runaway and spontaneous combustion due to overcharge of the battery. The application of existing aerogel materials in slurries has problems such as density difference and difficulty in mixing hydrophobic powders, which leads to Unsatisfactory performance and difficult processing.
Aerogel composite sheet made of glass fiber or pre-oxygen fiber felt as the base material, combined with silica aerogel slurry, flame retardant, binder, sunscreen and phase change microcapsules. The thermal insulation coating is formed by stirring, vacuum defoaming and roll coating techniques, and combined with oven drying to form a composite sheet.
It improves the thermal insulation and flame retardant properties of aerogel composite sheets, reduces production difficulty and environmental pollution, extends the service life of the battery pack, and effectively prevents fires under high temperature conditions.
Abstract
Description
Technical Field
[0001] The invention relates to an aerogel composite sheet and a preparation method thereof. Background Art
[0002] The power batteries of new energy vehicles are arranged in a specific way at the bottom of the vehicle and are firmly protected by a metal shell. Due to the characteristics of the power battery itself, fire accidents may occur when the battery is overcharged, short-circuited, or the battery management system fails. The dry climate in winter is prone to static electricity and sparks, which may cause the car to catch fire. Most of the spontaneous combustion of new energy vehicles starts from the power battery position, because there are many plastic parts here. Once the vehicle lines are aged, cracked or poorly contacted, short-circuited, leaked, or sparked, it may cause the car to catch fire. In low temperature environments, the cruising range of electric vehicles will be significantly reduced, and even more than half of the mileage will be lost. It is also difficult to charge low-temperature batteries. If the temperature drops below zero degrees Celsius, the mileage of electric vehicles will even be reduced by 30% compared to normal conditions.
[0003] Aerogel insulation materials can solve the problem of low temperature of new energy vehicle battery packs due to their low thermal conductivity, good thermal insulation effect, Class A fireproof performance, thin thickness, light weight, and easy use. Nanocomposite sheet aerogel insulation can withstand a 60-minute flame penetration test, meet RoHS testing standards, and produce no toxic or harmful gases under high temperature conditions. Only 1 / 5 to 1 / 3 of the thickness of traditional materials is needed to achieve the same thermal insulation effect, saving more valuable space for battery packs with limited space. The thermal insulation effect of the same thickness is more durable than that of traditional aerogel insulation materials, which can effectively solve the problem of reduced endurance of new energy battery packs in cold winter, improve power utilization efficiency, and extend the service life of battery packs. Under high temperature conditions, if there is no suitable heat dissipation solution, the temperature of each battery pack in the battery pack will be quite different, and the performance of adjacent battery packs will be affected by the excessive temperature of a battery pack. Among them, the more serious is the "thermal runaway" caused by overcharging of the battery, which in turn causes electric vehicles to catch fire and explode. The nano-composite sheet has Class A fireproof function and can also play a good thermal protection role when a new energy vehicle catches fire due to "thermal runaway", buying more time for passengers to escape or extinguish the fire, thereby reducing losses.
[0004] The use of silica aerogel slurry and fiber substrate composite is a simple and effective preparation method, but the application and development of aerogel materials in slurry is still very difficult for the following reasons: First, the density of aerogel materials is extremely low, which is very different from the density of other materials, and it is very difficult to disperse and mix in the slurry; second, hydrophobic aerogel powder is difficult to mix with other materials in an aqueous environment, resulting in the actual performance of the composite material is not ideal. In addition, silica aerogel insulation products, such as aerogel felt, often face the problem of aerogel powder falling off during use. When used on site, processing personnel need to do a strict dust protection, which increases processing costs. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide an aerogel composite sheet material, which has good heat insulation performance and flame retardant performance.
[0006] In order to solve the above technical problems, the technical solution of the present invention is:
[0007] An aerogel composite sheet comprises an upper substrate, an aerogel thermal insulation coating and a lower substrate bonded in sequence from top to bottom, wherein the upper substrate and the lower substrate are both glass fiber felt or preoxidized silk fiber felt, and the aerogel thermal insulation coating is made of the following components in parts by weight: 65-85 parts of aerogel slurry, 5-10 parts of flame retardant, 5-10 parts of binder, 0.5-1 part of sunscreen, and 5-10 parts of phase change microcapsules.
[0008] Furthermore, the aerogel slurry of the present invention is composed of silica aerogel, thixotropic colloid and surfactant in a weight ratio of (15-40):(60-80):(2-5); the thixotropic colloid is composed of a dispersant and water in a weight ratio of (1-3):(97-99), and the dispersant is one of hydroxypropyl cellulose, sodium alginate, casein, guar gum, starch or xanthan gum; the surfactant is one of polyethylene glycol distearate, sucrose monolaurate or fatty alcohol polyoxyethylene ether.
[0009] Furthermore, the flame retardant of the present invention is one of magnesium hydroxide, aluminum hydroxide or silicone flame retardant; the binder is one of waterborne polyurethane resin, waterborne acrylic resin or waterborne epoxy resin; the sunscreen is one of potassium hexatitanate whisker, aluminum oxide, white carbon black or magnesium oxide.
[0010] Furthermore, the preparation steps of the phase change microcapsules of the present invention are:
[0011] Paraffin and ethyl orthosilicate are mixed, stirred at 50°C until the paraffin melts, then a formamide solution containing hexadecyltrimethylammonium chloride is added dropwise, stirring is continued until a microemulsion is formed, then an aqueous hydrochloric acid solution is added dropwise, stirring is stopped after the reaction is carried out for 4 hours, and the product is obtained after aging at 60°C for 24 hours. The product is centrifuged for 10 minutes to obtain a precipitate, and the precipitate is washed 4 times with deionized water and anhydrous ethanol respectively, and dried at 80°C for 16 hours to obtain phase change microcapsules.
[0012] Furthermore, in the preparation steps of the phase change microcapsules described in the present invention, the ratio of paraffin, ethyl orthosilicate, hexadecyltrimethylammonium chloride, formamide, and hydrochloric acid aqueous solution is 8g:6mL:0.8g:120mL:100mL, and the concentration of the hydrochloric acid aqueous solution is 1.0mol / L; the stirring speed is 600rpm; and the centrifugal speed is 6000rpm.
[0013] Another technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned aerogel composite sheet.
[0014] To solve the above technical problems, the technical solution is:
[0015] A method for preparing an aerogel composite sheet comprises the following steps:
[0016] S1. The aerogel slurry, flame retardant, binder, sunscreen, and phase change microcapsules are mixed and added to a stirring tank and stirred for 30-60 minutes to obtain a mixed slurry;
[0017] S2. The mixed slurry obtained in step S1 is transferred into a negative pressure stirring tank and degassed by vacuum stirring for 20 minutes to obtain a defoamed slurry;
[0018] S3. The defoamed slurry obtained in step S2 is loaded into a roller coating device, and the surface of the lower substrate is evenly coated with a roller coating blade to form an aerogel thermal insulation coating;
[0019] S4. The lower substrate processed in step S3 is pulled to the composite pressing roller, the upper substrate is covered with the aerogel thermal insulation coating, and then pulled into the oven tunnel to obtain the aerogel composite sheet after drying.
[0020] Furthermore, in step S1 of the present invention, the stirring speed is 500-800 rpm.
[0021] Furthermore, in step S2 of the present invention, the negative pressure during vacuum stirring and degassing is -0.9 MPa, and the stirring speed during vacuum stirring and degassing is 600-1000 rpm.
[0022] Furthermore, the thickness of the upper substrate and the lower substrate of the present invention is 0.2-4 mm, and the thickness of the aerogel thermal insulation coating is 3 mm.
[0023] Furthermore, in step S4 of the present invention, the pulling speed when pulling to the composite pressing roller is 5-10 m / min, and the roller gap at the composite pressing roller is 3 mm; the pulling speed when pulling to the oven tunnel is 1-1.5 m / min; and the drying temperature is 70-120°C.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1) The silica aerogel-containing slurry used in the present invention is an aqueous slurry without organic solvent components, has little environmental pollution, and improves production safety; the present invention also uses a surfactant to modify the surface of the hydrophobic silica aerogel, reduces the agglomeration phenomenon in the slurry, and improves the dispersion effect of the slurry; at the same time, since the slurry is vacuum degassed, the bubble problem in the slurry is effectively solved, and the slurry properties are kept stable, the construction performance of the slurry and the performance of the aerogel composite sheet are improved, and the production efficiency is also improved.
[0026] 2) The present invention prepares aerogel composite sheets by a secondary molding method rather than a sol-gel method, which does not require supercritical conditions, effectively reduces the production difficulty, simplifies the production process, and requires relatively simple equipment. Therefore, the present invention is a cost-effective and preferred solution for preparing high-quality thermal insulation materials.
[0027] 3) The phase change microcapsules prepared by the present invention can effectively improve the thermal insulation performance of the composite sheet: the phase change microcapsules are composed of an inner core and an outer shell. The inner core is a phase change material, which absorbs a large amount of heat when a phase change occurs, and can delay or inhibit the spread of heat, thereby achieving a better thermal insulation effect. Compared with traditional phase change materials, phase change microcapsules can effectively increase the heat transfer area, and at the same time can well control the volume change of the material during phase transition, so that the morphology of the system remains basically unchanged, thereby improving the stability of the phase change material. In addition, phase change microcapsules are easy to encapsulate, can reduce the toxicity of phase change materials, and are green, environmentally friendly and pollution-free. DETAILED DESCRIPTION
[0028] The present invention will be described in detail below in conjunction with specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.
[0029] Example 1
[0030] The aerogel composite sheet includes an upper substrate, an aerogel thermal insulation coating and a lower substrate bonded in sequence from top to bottom, the upper substrate and the lower substrate are both glass fiber felt, and the aerogel thermal insulation coating is made of the following components in parts by weight: 65 parts of aerogel slurry, 6 parts of flame retardant, 5 parts of binder, 0.7 parts of sunscreen, and 5 parts of phase change microcapsules. The flame retardant is magnesium hydroxide, the binder is water-based acrylic resin, and the sunscreen is potassium hexatitanate whisker.
[0031] The aerogel slurry is composed of silica aerogel, thixotropic colloid and surfactant in a weight ratio of 30:68:2; the thixotropic colloid is composed of dispersant and water in a weight ratio of 2:98, the dispersant is hydroxypropyl cellulose, and the surfactant is sucrose monolaurate.
[0032] The preparation steps of phase change microcapsules are:
[0033] Paraffin wax and tetraethyl orthosilicate were mixed, stirred at 600 rpm and 50°C until the paraffin melted, then a formamide solution containing hexadecyltrimethylammonium chloride was added dropwise, and stirring was continued until a microemulsion was formed, then a 1.0 mol / L hydrochloric acid aqueous solution was added dropwise, and the stirring was stopped after the reaction was stirred for 4 hours. The product was aged at 60°C for 24 hours to obtain a precipitate, and the product was aged at 6000 rpm for 10 minutes to obtain a precipitate. The precipitate was washed 4 times with deionized water and anhydrous ethanol respectively, and dried at 80°C for 16 hours to obtain phase change microcapsules; the ratio of paraffin wax, tetraethyl orthosilicate, hexadecyltrimethylammonium chloride, formamide, and hydrochloric acid aqueous solution was 8g:6mL:0.8g:120mL:100mL.
[0034] The preparation method of Example 1 comprises the following steps:
[0035] S1. The aerogel slurry, flame retardant, binder, sunscreen, and phase change microcapsules were mixed and added to a stirring tank and stirred at 650 rpm for 45 min to obtain a mixed slurry;
[0036] S2. The mixed slurry obtained in step S1 is transferred into a negative pressure stirring tank, and the deaerated slurry is obtained by vacuum stirring and degassing for 20 minutes. The negative pressure during vacuum stirring and degassing is -0.9MPa, and the stirring speed during vacuum stirring and degassing is 700rpm;
[0037] S3. The defoamed slurry obtained in step S2 is loaded into a roller coating device, and the surface of the lower substrate is evenly coated with a roller coating blade to form an aerogel thermal insulation coating;
[0038] S4. The lower substrate treated in step S3 is pulled to the composite press roller at a pulling speed of 6 m / min, the upper substrate is covered with the aerogel thermal insulation coating, and then pulled into the oven tunnel at a pulling speed of 1 m / min, and dried at 70°C to obtain an aerogel composite sheet, wherein the thickness of the upper substrate and the lower substrate is 0.43 mm, the thickness of the aerogel thermal insulation coating is 3 mm, and the roller gap at the composite press roller is 3 mm.
[0039] Example 2
[0040] The aerogel composite sheet comprises an upper substrate, an aerogel thermal insulation coating and a lower substrate bonded in sequence from top to bottom, the upper substrate and the lower substrate are both pre-oxidized silk fiber felt, and the aerogel thermal insulation coating is made of the following components in parts by weight: 75 parts of aerogel slurry, 8 parts of flame retardant, 7 parts of binder, 0.8 parts of sunscreen, and 8 parts of phase change microcapsules. The flame retardant is magnesium hydroxide, the binder is waterborne polyurethane resin, and the sunscreen is aluminum oxide.
[0041] The aerogel slurry is composed of silica aerogel, thixotropic colloid and surfactant in a weight ratio of 25:70:3; the thixotropic colloid is composed of dispersant and water in a weight ratio of 2:98, the dispersant is casein, and the surfactant is polyethylene glycol distearate.
[0042] The preparation steps of phase change microcapsules are the same as those in Example 1.
[0043] The preparation method of Example 2 comprises the following steps:
[0044] S1. The aerogel slurry, flame retardant, binder, sunscreen, and phase change microcapsules were mixed and added to a stirring tank and stirred at 800 rpm for 60 min to obtain a mixed slurry;
[0045] S2. The mixed slurry obtained in step S1 is transferred into a negative pressure stirring tank, and the deaerated slurry is obtained by vacuum stirring and degassing for 20 minutes. The negative pressure during vacuum stirring and degassing is -0.9MPa, and the stirring speed during vacuum stirring and degassing is 800rpm;
[0046] S3. The defoamed slurry obtained in step S2 is loaded into a roller coating device, and the surface of the lower substrate is evenly coated with a roller coating blade to form an aerogel thermal insulation coating;
[0047] S4. The lower substrate treated in step S3 is pulled to the composite pressing roller at a pulling speed of 5 m / min, the upper substrate is covered with the aerogel thermal insulation coating, and then pulled into the oven tunnel at a pulling speed of 1.2 m / min. After drying at 100° C., an aerogel composite sheet is obtained. The thickness of the upper substrate and the lower substrate is 1 mm, the thickness of the aerogel thermal insulation coating is 3 mm, and the roller gap at the composite pressing roller is 3 mm.
[0048] Example 3
[0049] The aerogel composite sheet includes an upper substrate, an aerogel thermal insulation coating and a lower substrate bonded in sequence from top to bottom, the upper substrate and the lower substrate are both glass fiber felt, and the aerogel thermal insulation coating is made of the following components in parts by weight: 80 parts of aerogel slurry, 7 parts of flame retardant, 7 parts of binder, 0.7 parts of sunscreen, and 5 parts of phase change microcapsules. The flame retardant is aluminum hydroxide, the binder is water-based acrylic resin, and the sunscreen is white carbon black.
[0050] Among them, the aerogel slurry is composed of silica aerogel, thixotropic colloid and surfactant in a weight ratio of 30:67:3; the thixotropic colloid is composed of dispersant and water in a weight ratio of 3:97, the dispersant is sodium alginate, and the surfactant is sucrose monolaurate.
[0051] The preparation steps of phase change microcapsules are the same as those in Example 1.
[0052] The preparation method of Example 3 comprises the following steps:
[0053] S1. The aerogel slurry, flame retardant, binder, sunscreen, and phase change microcapsules were mixed and added to a stirring tank and stirred at 750 rpm for 50 min to obtain a mixed slurry;
[0054] S2. The mixed slurry obtained in step S1 is transferred into a negative pressure stirring tank, and the deaerated slurry is obtained by vacuum stirring and degassing for 20 minutes. The negative pressure during vacuum stirring and degassing is -0.9MPa, and the stirring speed during vacuum stirring and degassing is 800rpm;
[0055] S3. The defoamed slurry obtained in step S2 is loaded into a roller coating device, and the surface of the lower substrate is evenly coated with a roller coating blade to form an aerogel thermal insulation coating;
[0056] S4. The lower substrate treated in step S3 is pulled to the composite press roller at a pulling speed of 7 m / min, the upper substrate is covered with the aerogel thermal insulation coating, and then pulled into the oven tunnel at a pulling speed of 1.1 m / min. After drying at 90° C., an aerogel composite sheet is obtained. The thickness of the upper substrate and the lower substrate is 0.4 mm, the thickness of the aerogel thermal insulation coating is 3 mm, and the roller gap at the composite press roller is 3 mm.
[0057] Comparative Example 1: The difference from Example 1 is that phase change microcapsules and the preparation steps thereof are not included.
[0058] Comparative Example 2: The difference from Example 2 is that phase change microcapsules and their preparation steps are not included.
[0059] Comparative Example 3: The difference from Example 3 is that phase change microcapsules and their preparation steps are not included.
[0060] Experimental Example 1: Thermal insulation performance test
[0061] 1. The test samples are the aerogel composite sheets prepared in Examples 1-3 and Comparative Examples 1-3. The density of the samples is recorded. The surfaces of the heating plate and the thick aluminum plate are cleaned to make them clean.
[0062] 2. Set the heater temperature to the specified temperature of 600±15℃ and start heating;
[0063] 3. After the heater temperature stabilizes at 600°C, quickly place the sample on the heating table, start timing, arrange the thick aluminum plate and pressure sensor, and apply a stress of 0.9±0.04MPa;
[0064] 4. Keep warm for 10 minutes, first turn off the multi-channel thermometer recording function, then turn off the intelligent heater switch, use a plug gauge to check the thickness of the sample and record and save the multi-channel temperature after the experiment, and keep the hot surface of the sample after the experiment, and measure the thermal insulation temperature difference of each sample. The higher the thermal insulation temperature difference, the better the thermal insulation performance.
[0065] The test results are shown in Table 1:
[0066] Sample name Insulation temperature difference / ℃ Example 1 505 Example 2 511 Example 3 500 Comparative Example 1 474 Comparative Example 2 478 Comparative Example 3 470
[0067] Table 1
[0068] As can be seen from Table 1, the thermal insulation temperature differences of Examples 1-3 of the present invention are all relatively high, indicating that the aerogel composite sheet prepared by the present invention has good thermal insulation performance. In addition, the thermal insulation temperature differences of Examples 1-3 are significantly higher than those of Comparative Examples 1-3, indicating that the phase change microcapsules prepared by the present invention can effectively improve the thermal insulation performance of the aerogel composite sheet.
[0069] Experimental Example 2: Flame retardant performance test
[0070] The test samples are the aerogel composite sheets prepared in Examples 1-3 and Comparative Examples 1-3. The oxygen index of the samples is measured using an oxygen index meter in accordance with GB / T 2406-2009. The higher the oxygen index, the better the flame retardant performance. The test results are shown in Table 2:
[0071] Sample name Oxygen index / % Example 1 30.8 Example 2 31.2 Example 3 30.5 Comparative Example 1 29.4 Comparative Example 2 29.9 Comparative Example 3 29.0
[0072] Table 2
[0073] As can be seen from Table 2, the oxygen indexes of Examples 1-3 of the present invention are all relatively high, indicating that the aerogel composite sheet prepared by the present invention has good flame retardant properties. In addition, the oxygen indexes of Comparative Examples 1-3 are all lower than those of Examples 1-3, indicating that the phase change microcapsules prepared by the present invention can also play a certain role in improving the flame retardant properties of the aerogel composite sheet.
[0074] Example 4
[0075] The aerogel composite sheet comprises an upper substrate, an aerogel thermal insulation coating and a lower substrate bonded in sequence from top to bottom, the upper substrate and the lower substrate are both pre-oxidized silk fiber felt, and the aerogel thermal insulation coating is made of the following components in parts by weight: 85 parts of aerogel slurry, 5 parts of flame retardant, 8 parts of binder, 0.5 parts of sunscreen, and 9 parts of phase change microcapsules. The flame retardant is aluminum hydroxide, the binder is water-based epoxy resin, and the sunscreen is magnesium oxide.
[0076] The aerogel slurry is composed of silica aerogel, thixotropic colloid and surfactant in a weight ratio of 15:80:5; the thixotropic colloid is composed of dispersant and water in a weight ratio of 1:99, the dispersant is guar gum, and the surfactant is fatty alcohol polyoxyethylene ether.
[0077] The preparation steps of phase change microcapsules are the same as those in Example 1.
[0078] The preparation method of Example 4 comprises the following steps:
[0079] S1. The aerogel slurry, flame retardant, binder, sunscreen, and phase change microcapsules were mixed and added to a stirring tank and stirred at 500 rpm for 60 min to obtain a mixed slurry;
[0080] S2. The mixed slurry obtained in step S1 is transferred into a negative pressure stirring tank, and the deaerated slurry is obtained by vacuum stirring and degassing for 20 minutes. The negative pressure during vacuum stirring and degassing is -0.9MPa, and the stirring speed during vacuum stirring and degassing is 600rpm;
[0081] S3. The defoamed slurry obtained in step S2 is loaded into a roller coating device, and the surface of the lower substrate is evenly coated with a roller coating blade to form an aerogel thermal insulation coating;
[0082] S4. The lower substrate treated in step S3 is pulled to the composite pressing roller at a pulling speed of 10 m / min, the upper substrate is covered with the aerogel thermal insulation coating, and then pulled into the oven tunnel at a pulling speed of 1.5 m / min. After drying at 120° C., an aerogel composite sheet is obtained. The thickness of the upper substrate and the lower substrate is 0.2 mm, the thickness of the aerogel thermal insulation coating is 3 mm, and the roller gap at the composite pressing roller is 3 mm.
[0083] Example 5
[0084] The aerogel composite sheet comprises an upper substrate, an aerogel thermal insulation coating and a lower substrate bonded in sequence from top to bottom, the upper substrate and the lower substrate are both pre-oxidized silk fiber felt, and the aerogel thermal insulation coating is made of the following components in parts by weight: 70 parts of aerogel slurry, 10 parts of flame retardant, 6 parts of binder, 1 part of sunscreen, and 10 parts of phase change microcapsules. The flame retardant is an organic silicon flame retardant, the binder is an aqueous polyurethane resin, and the sunscreen is a potassium hexatitanate whisker.
[0085] The aerogel slurry is composed of silica aerogel, thixotropic colloid and surfactant in a weight ratio of 40:60:2; the thixotropic colloid is composed of dispersant and water in a weight ratio of 1:99, the dispersant is starch, and the surfactant is fatty alcohol polyoxyethylene ether.
[0086] The preparation steps of phase change microcapsules are the same as those in Example 1.
[0087] The preparation method of Example 5 comprises the following steps:
[0088] S1. The aerogel slurry, flame retardant, binder, sunscreen, and phase change microcapsules were mixed and added to a stirring tank and stirred at 600 rpm for 60 min to obtain a mixed slurry;
[0089] S2. The mixed slurry obtained in step S1 is transferred into a negative pressure stirring tank, and the deaerated slurry is obtained by vacuum stirring and degassing for 20 minutes. The negative pressure during vacuum stirring and degassing is -0.9MPa, and the stirring speed during vacuum stirring and degassing is 900rpm;
[0090] S3. The defoamed slurry obtained in step S2 is loaded into a roller coating device, and the surface of the lower substrate is evenly coated with a roller coating blade to form an aerogel thermal insulation coating;
[0091] S4. The lower substrate treated in step S3 is pulled to the composite pressing roller at a pulling speed of 5 m / min, the upper substrate is covered with the aerogel thermal insulation coating, and then pulled into the oven tunnel at a pulling speed of 1 m / min, and dried at 80°C to obtain an aerogel composite sheet, wherein the thickness of the upper substrate and the lower substrate is 4 mm, the thickness of the aerogel thermal insulation coating is 3 mm, and the roller gap at the composite pressing roller is 3 mm.
[0092] Example 6
[0093] The aerogel composite sheet includes an upper substrate, an aerogel thermal insulation coating and a lower substrate bonded in sequence from top to bottom, the upper substrate and the lower substrate are both glass fiber felt, and the aerogel thermal insulation coating is made of the following components in parts by weight: 72 parts of aerogel slurry, 9 parts of flame retardant, 10 parts of binder, 0.6 parts of sunscreen, and 8 parts of phase change microcapsules. The flame retardant is an organic silicon flame retardant, the binder is a water-based epoxy resin, and the sunscreen is aluminum oxide.
[0094] The aerogel slurry is composed of silica aerogel, thixotropic colloid and surfactant in a weight ratio of 25:70:4; the thixotropic colloid is composed of dispersant and water in a weight ratio of 3:97, the dispersant is xanthan gum, and the surfactant is polyethylene glycol distearate.
[0095] The preparation steps of phase change microcapsules are the same as those in Example 1.
[0096] The preparation method of Example 6 comprises the following steps:
[0097] S1. The aerogel slurry, flame retardant, binder, sunscreen, and phase change microcapsules were mixed and added to a stirring tank and stirred at 800 rpm for 30 min to obtain a mixed slurry;
[0098] S2. The mixed slurry obtained in step S1 is transferred into a negative pressure stirring tank, and the deaerated slurry is obtained by vacuum stirring and degassing for 20 minutes. The negative pressure during vacuum stirring and degassing is -0.9MPa, and the stirring speed during vacuum stirring and degassing is 1000rpm;
[0099] S3. The defoamed slurry obtained in step S2 is loaded into a roller coating device, and the surface of the lower substrate is evenly coated with a roller coating blade to form an aerogel thermal insulation coating;
[0100] S4. The lower substrate treated in step S3 is pulled to the composite press roller at a pulling speed of 8 m / min, the upper substrate is covered with the aerogel thermal insulation coating, and then pulled into the oven tunnel at a pulling speed of 1.2 m / min. After drying at 110° C., an aerogel composite sheet is obtained. The thickness of the upper substrate and the lower substrate is 2 mm, the thickness of the aerogel thermal insulation coating is 3 mm, and the roller gap at the composite press roller is 3 mm.
[0101] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. An aerogel composite sheet, characterized in that: The invention comprises an upper substrate, an aerogel thermal insulation coating and a lower substrate bonded in sequence from top to bottom, wherein the upper substrate and the lower substrate are both glass fiber felt or preoxidized silk fiber felt, and the aerogel thermal insulation coating is made of the following components in parts by weight: 65-85 parts of aerogel slurry, 5-10 parts of flame retardant, 5-10 parts of binder, 0.5-1 part of sunscreen, and 5-10 parts of phase change microcapsules.
2. The aerogel composite sheet according to claim 1, characterized in that: The aerogel slurry is composed of silica aerogel, thixotropic colloid and surfactant in a weight ratio of (15-40):(60-80):(2-5); the thixotropic colloid is composed of a dispersant and water in a weight ratio of (1-3):(97-99), and the dispersant is one of hydroxypropyl cellulose, sodium alginate, casein, guar gum, starch or xanthan gum; the surfactant is one of polyethylene glycol distearate, sucrose monolaurate or fatty alcohol polyoxyethylene ether.
3. The aerogel composite sheet according to claim 1, characterized in that: The flame retardant is one of magnesium hydroxide, aluminum hydroxide or silicone flame retardant; the binder is one of waterborne polyurethane resin, waterborne acrylic resin or waterborne epoxy resin; the sunscreen is one of potassium hexatitanate whisker, aluminum oxide, white carbon black or magnesium oxide.
4. The aerogel composite sheet according to claim 1, characterized in that: The preparation steps of the phase change microcapsules are: Paraffin and ethyl orthosilicate are mixed, stirred at 50°C until the paraffin melts, then a formamide solution containing hexadecyltrimethylammonium chloride is added dropwise, stirring is continued until a microemulsion is formed, then an aqueous hydrochloric acid solution is added dropwise, stirring is stopped after the reaction is carried out for 4 hours, and the product is obtained after aging at 60°C for 24 hours. The product is centrifuged for 10 minutes to obtain a precipitate, and the precipitate is washed 4 times with deionized water and anhydrous ethanol respectively, and dried at 80°C for 16 hours to obtain phase change microcapsules.
5. The aerogel composite sheet according to claim 4, characterized in that: In the preparation steps of the phase change microcapsules, the ratio of paraffin, ethyl orthosilicate, hexadecyltrimethylammonium chloride, formamide, and hydrochloric acid aqueous solution is 8g:6mL:0.8g:120mL:100mL, and the concentration of the hydrochloric acid aqueous solution is 1.0mol / L; the stirring speed is 600rpm; and the centrifugal speed is 6000rpm.
6. The method for preparing an aerogel composite sheet according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. The aerogel slurry, flame retardant, binder, sunscreen, and phase change microcapsules are mixed and added to a stirring tank and stirred for 30-60 minutes to obtain a mixed slurry; S2. The mixed slurry obtained in step S1 is transferred into a negative pressure stirring tank and degassed by vacuum stirring for 20 minutes to obtain a defoamed slurry; S3. The defoamed slurry obtained in step S2 is loaded into a roller coating device, and the surface of the lower substrate is evenly coated with a roller coating blade to form an aerogel thermal insulation coating; S4. The lower substrate processed in step S3 is pulled to the composite pressing roller, the upper substrate is covered with the aerogel thermal insulation coating, and then pulled into the oven tunnel to obtain the aerogel composite sheet after drying.
7. The method for preparing an aerogel composite sheet according to claim 6, characterized in that: In the step S1, the stirring speed is 500-800 rpm.
8. The method for preparing an aerogel composite sheet according to claim 6, characterized in that: In the step S2, the negative pressure during vacuum stirring and degassing is -0.9 MPa, and the stirring speed during vacuum stirring and degassing is 600-1000 rpm.
9. The method for preparing an aerogel composite sheet according to claim 6, characterized in that: The thickness of the upper substrate and the lower substrate is 0.2-4 mm, and the thickness of the aerogel thermal insulation coating is 3 mm.
10. The method for preparing an aerogel composite sheet according to claim 6, characterized in that: In the step S4, the pulling speed when pulling to the composite pressing roller is 5-10 m / min, and the roller gap at the composite pressing roller is 3 mm; the pulling speed when pulling to the oven tunnel is 1-1.5 m / min; and the drying temperature is 70-120°C.
Citation Information
Patent Citations
Halogen-free flame-retardant temperature controlled microcapsules and preparation method thereof
CN104650929A
Phase change aerogel composite coatings and their preparation methods, heat insulation pads
CN114934393A
Silicon dioxide aerogel battery cell heat insulation sheet and preparation method thereof
CN116945715A
Composite of aerogel and phase change material
US20070290392A1
Cited By
Pre-oxidized fiber aerogel composite adhesive tape for power battery and application of pre-oxidized fiber aerogel composite adhesive tape
CN122543287A